Protocol of the PLeural Effusion And Symptom Evaluation (PLEASE) study on the pathophysiology of breathlessness in patients with symptomatic pleural effusions. Issue 8 (3rd August 2016) - Thomas, Rajesh; Azzopardi, Maree; Muruganandan, Sanjeevan; Read, Catherine; Murray, Kevin; Eastwood, Peter; Jenkins, Sue; Singh, Bhajan; Lee, Y C Gary
Abstract : Introduction: Pleural effusion is a common clinical problem that can complicate many medical conditions. Breathlessness is the most common symptom of pleural effusion of any cause and the most common reason for pleural drainage. However, improvement in breathlessness following drainage of an effusion is variable; some patients experience either no benefit or a worsening of their breathlessness. The physiological mechanisms underlying breathlessness in patients with a pleural effusion are unclear and likely to be multifactorial with patient-related and effusion-related factors contributing. A comprehensive study of the physiological and symptom responses to drainage of pleural effusions may provide a clearer understanding of these mechanisms, and may identify predictors of benefit from drainage. The ability to identify those patients whose breathlessness will (or will not) improve after pleural fluid drainage can help avoid unnecessary pleural drainage procedures, their associated morbidities and costs. The PLeural Effusion And Symptom Evaluation (PLEASE) study is a prospective study to comprehensively evaluate factors contributing to pleural effusion-related breathlessness. Methods and analysis: The PLEASE study is a single-centre prospective study of 150 patients with symptomatic pleural effusions that require therapeutic drainage. The study aims to identify key factors that underlie breathlessness in patients with pleural effusions and develop predictors of improvement in breathlessness following effusion drainage. Participants will undergo evaluation pre-effusion and post-effusion drainage to assess their level of breathlessness at rest and during exercise, respiratory and other physiological responses as well as respiratory muscle mechanics. Pre-drainage and post-drainage parameters will be collected and compared to identify the key factors and mechanisms that correlate with improvement in breathlessness. Ethics and dissemination: Approved by the Sir Charles Gairdner Group Human Research Ethics Committee (HREC number 2014-079). Registered with the Australian New Zealand Clinical Trials Registry (ACTRN12616000820404). Results will be published in peer-reviewed journals and presented at scientific meetings. Trial registration number: ACTRN12616000820404; Pre-results.